Desarrollo de un sistema de gestión de relaciones con el cliente para la Empresa Said Group (2021)
The purpose of this project is the development of a system that, through a web interface divided into modules, allows to control the products and services provided by the company and the registration of customers quickly and easily, with the In order to improve the quality of the service and guarantee customer satisfaction, thereby avoiding economic losses to the company.